Analisis Infrastruktur Jalan dan Pendidikan Sebagai Tantangan Demokrasi dan Tata Kelola di Provinsi Papua Barat - Bella Ola Shakira; Najwa Adhwa Ramadhani; Zahra Hanifah Salma; Ardhana Ulfa Azis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The lack of road infrastructure in West Papua is a complex problem that has a major impact on the lives of local people. Road development in West Papua is still far behind compared to other regions in Indonesia. The lack of road infrastructure also affects access to education in West Papua. Adequate education is essential in improving the quality of life and opening up opportunities for communities to develop. The purpose of this study is to examine how road infrastructure and education affect governance and democracy in West Papua. The results show that inequality in road infrastructure and education has an impact on limited access to public services, social welfare, and community democratic participation. Using a descriptive qualitative approach based on secondary data, this research illustrates that good governance is needed to overcome geographical barriers and inequality in resource distribution to enhance sustainable development in underdeveloped regions.